Antioxidant activity, anti-tyrosinase activity, molecular docking studies, and molecular dynamic simulation of active compounds found in nipa palm vinegar - Chatatikun, Moragot; Tedasen, Aman; Pattaranggoon, Nawanwat Chainuwong; Palachum, Wilawan; Chuaijit, Sirithip; Mudpan, Amron; Pruksaphanrat, Supawita; Sohbenalee, Sasirat; Yamasaki, Kenshi; Klangbud, Wiyada Kwanhian (PeerJ, 2023)
Tyrosinase is a key enzyme in melanogenesis and its inhibitors have become increasingly because of their potential activity as hypopigmenting agents which have less side effects. Nipa palm vinegar is an aqueous product that is normally used as a food supplement. The aim of this study was to study the determination of antioxidant activity and tyrosinase inhibitory activities of aqueous extract of original nipa palm vinegar (AE O-NPV), nipa palm vinegar powder (NPV-P) and aqueous extract of nipa palm vinegar powder (AE NPV-P) were examined. Nipa palm vinegars were evaluated the phenolic and flavonoid content, and the active compounds which were submitted to molecular docking and molecular dynamic simulation, chemoinformatics, rule of five, skin absorption and toxicity. The highest phenolic and flavonoid contents in the AE O-NPV were 2.36 ± 0.23 mg gallic acid equivalents/g extract and 5.11 ± 0.59 mg quercetin equivalents/g, and the highest ABTS radical cation scavenging activity was also found. The AE O-NPV, NPV-P and AE NPV-P showed anti-mushroom tyrosinase activity. The HPLC analysis showed that there were vanillic acid and three flavonoids (catechin, rutin and quercetin). The molecular docking study revealed that the binding of the vanillic acid and three flavonoids occurred in the active site residues (histidine and other amino acids). Moreover, the number of hydrogen bond acceptors/donors, solubility, polar surface area and bioavailability score of the vanillic acid and three flavonoids were acceptable compared to Lipinski’s Rule of Five. The molecular dynamic simulation showed that vanillic acid interacts with HIS284 through π–π stacking hydrophobic interactions and forms a metal-acceptor interaction with the copper molecule at the tyrosinase active site. All compounds revealed good skin permeability and nontoxicity. Nipa palm vinegar could be a promising source of a new ingredient for tyrosinase inhibition for cosmetics or pharmaceutical products.
Keywords: Nypa fruticans Wurmb; Antioxidant; Molecular docking; Nipa palm vinegar; Molecular dynamic; Tyrosinase inhibitor